82.8k views
3 votes
Please solve and explain how. Photo attached

Please solve and explain how. Photo attached-example-1
User Janil
by
5.2k points

1 Answer

3 votes

The solution is
x=14

Step-by-step explanation:

The given expression is
(6)/(x^(2) -3x)=(1)/(x)- (5)/(x^(2) -3x)

We need to determine the solution of the expression.

Let us simplify the equation by taking LCM on both sides.

The LCM of
x^(2) -3x is
x(x-3)

Thus, we have,


(6)/(x^(2) -3x)x(x-3)=(1)/(x)x(x-3)- (5)/(x^(2) -3x)x(x-3)

Simplifying the terms, we get,


6=x-3-5

Subtracting the terms, we have,


6=x-8

Subtracting both sides of the expression by 6, we get,


0=x-14

Adding both sides of the expression by 14, we have,


14=x

Thus, the solution of the equation is
x=14

User Timothy Gu
by
5.3k points